Real‐time correction by optical tracking with integrated geometric distortion correction for reducing motion artifacts in functional MRI. Issue 3 (14th May 2012) - Rotenberg, David; Chiew, Mark; Ranieri, Shawn; Tam, Fred; Chopra, Rajiv; Graham, Simon J.
Abstract Head motion artifacts are a major problem in functional MRI that limit its use in neuroscience research and clinical settings. Real‐time scan‐plane correction by optical tracking has been shown to correct slice misalignment and nonlinear spin‐history artifacts; however, residual artifacts due to dynamic magnetic field nonuniformity may remain in the data. A recently developed correction technique, Phase Labeling for Additional Coordinate Encoding, can correct for absolute geometric distortion using only the complex image data from two echo planar images with slightly shifted k‐space trajectories. An approach is presented that integrates Phase Labeling for Additional Coordinate Encoding into a real‐time scan‐plane update system by optical tracking, applied to a tissue‐equivalent phantom undergoing complex motion and an functional MRI finger tapping experiment with overt head motion to induce dynamic field nonuniformity. Experiments suggest that such integrated volume‐by‐volume corrections are very effective at artifact suppression, with potential to expand functional MRI applications. Magn Reson Med, 2013. © 2012 Wiley Periodicals, Inc.